August, Rebecca Beck (audio interview #3 of 3) - August, Rebecca Beck (b. 1/1/1883 - 08//1978); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - In this third and final interview with Rebecca August , conducted in her room at the Jewish Home for the Aged, the narrator seemed be become somewhat confused about time periods as the interview progressed. This is particularly evident when she discussed the two different times in which she was involved with the Home Colony in Washington. Throughout the interview, August recounts her activities in rather broad and somewhat grandiose terms, with details lacking. TOPICS - marriage; childbirth; child care; work; organizing efforts in Seattle; women's branch of the Workmen's Circle; and her attitudes towards feminism;activities in LA ACWA; the development of the Retiree's Club of the ACWA; activities in the 1920s; disillusionment with radicalism in the 1920s; relationship with her second husband; and her thoughts on feminism and the status of women today; 3/19/1973